Examining Land Rights Expropriation Policies for Public Interest: A Social Justice Perspective in Indonesia - Noor, Aslan; Alamsyah, Dian; Fathurrohman, Mohammad Faridz (Manunggal Halim Jaya, 2026)
The policy of land acquisition for public purposes is an important instrument for supporting national development. Yet in practice, it often generates agrarian conflicts and raises concerns about justice for affected communities. The central issue lies in the gap between the normative objectives of land acquisition policies and their implementation, particularly in ensuring the protection of citizens' rights and the realization of social justice. This study addresses the following research question: How is the implementation of land acquisition policies for public interest evaluated from a social justice perspective? Using a normative legal research method, this study analyses relevant legislation, court decisions, and recent academic literature through statutory, conceptual, and case approaches. The findings reveal that land acquisition practices remain dominated by administrative and legal-formal orientations, which limit the achievement of substantive justice. Community participation is often procedural rather than meaningful, compensation mechanisms largely emphasize economic valuation, and restorative measures to support post-displacement recovery are insufficiently integrated. The study concludes that land acquisition policies must be reoriented toward a more participatory, equitable, and restorative framework to strengthen policy legitimacy and better safeguard community rights throughout the development process.